Pediatrični medicinski stres in travma - Škorjanc, Jana (Psihološka obzorja (Ljubljana), 2021)
Events related to various illnesses, injuries and chronic conditions, as well as related treatment and medical interventions, represent the most common potential traumatic experiences in childhood. In the article, the author inquires about the occurrence of traumatic stress and medical trauma in children and their families. A theoretical model of long-term somatic threat designed to distinguish between medical trauma and trauma not caused by medical events can be used to identify medical trauma. Various studies report that up to 80% of children and their families experience some traumatic stress in dealing with life-threatening illnesses, injuries or painful medical procedures. About 20-30% of parents and 15-25% of children and their relatives even experience lasting traumatic stress that impedes daily functioning and affects the very course of treatment and recovery. The development and course of pediatric medical trauma is exemplified by the model of pediatric medical traumatic stress, which also outlines the goals of interventions for each stage of the course. In addition to the psychologist, health care staff also play an important role in preventing the trauma that can occur when treating children, adolescents and their parents. All professionals and healthcare professionals should strive to address and care for children, including awareness of and informing about trauma, and thus prevent or reduce the negative effects of trauma that can occur in the medical environment.
Keywords: adolescents; children; intensive care; intenzivna nega; mladostniki; otroci; parents; pediatric medical traumatic stress PMTS; pediatrični medicinski travmatski stres PMTS; starši; trauma; travma